Effects of stretching before intense exercise training on hematologic and cellular injury indices - N. Lotfi; S. Mohamadi; M. Mirzaei-Takmil (H.S. Skovoroda Kharkov National Pedagogical University, 2018)
Purpose: The aim of the study was to investigate the effect of stretching before intense exercise on hematologic parameters and cell injury. Subjects: The subjects of the present study were 12 adolescent members of the Kurdistan Province futsal team (age: 14.83 ± 0.38 years, height: 173.92 ± 5.90 cm, weight: 63.50 ± 7.94 kg, peak power: 459.42 ± 95.94 watts). The RAST test was used to estimate the anaerobic power and to create the training load. Indexes of blood including white and red blood cells, hemoglobin, hematocrit, platelet and the levels of CK and LDH enzyme activities were measured. Results: The results of the pre and the post tests showed that among hematological parameters and cell damage indexes, the red blood cell and hemoglobin in both groups and the level of LDH in the training group were not significantly changed (p>0.05). Other parameters in the pre-test and post-test measures were statistically changed (p<0.05). Conclusion: Based on the results of the present study, it seems that stretching before intense training decreases the cell damage and side effects of exercise training on the hematological factors.